2023
DOI: 10.3390/ph16070959
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B2 Receptor Mediates Cisplatin-Induced Painful Peripheral Neuropathy by Intracellular Kinase Pathways and TRPA1 Channel Sensitisation

Abstract: Chemotherapy-induced peripheral neuropathy is a severe clinical problem frequently associated with cisplatin use. Although its pathophysiology is poorly understood, it is known that kinin receptors and the transient receptor potential ankyrin 1 (TRPA1) channel play a significant role in the peripheral neuropathy induced by cisplatin in rodents. However, the role of signalling pathways downstream from B2 kinin receptors activation and sensitisation of the TRPA1 channel remains unknown in this model. The cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In this sense, recent studies using pharmacological antagonism and genetic manipulation have demonstrated the contribution of kinin B 1 and B 2 receptors to the painful behaviours of cisplatin-induced peripheral neuropathy [54]. Furthermore, it was observed that PLC and protein kinase C epsilon (PKCε) intracellular signalling pathways downstream from the kinin B 2 receptor activation are involved in the transient receptor potential ankyrin 1 (TRPA1) channel sensitization, contributing to the painful behaviours caused by cisplatin in mice [55]. Thus, kinin receptor antagonists present themselves as promising pharmacological strategies for treating cisplatin-induced peripheral neuropathy (Figure 2).…”
Section: Role Of G Protein-coupled Receptors In Cisplatin-induced Per...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, recent studies using pharmacological antagonism and genetic manipulation have demonstrated the contribution of kinin B 1 and B 2 receptors to the painful behaviours of cisplatin-induced peripheral neuropathy [54]. Furthermore, it was observed that PLC and protein kinase C epsilon (PKCε) intracellular signalling pathways downstream from the kinin B 2 receptor activation are involved in the transient receptor potential ankyrin 1 (TRPA1) channel sensitization, contributing to the painful behaviours caused by cisplatin in mice [55]. Thus, kinin receptor antagonists present themselves as promising pharmacological strategies for treating cisplatin-induced peripheral neuropathy (Figure 2).…”
Section: Role Of G Protein-coupled Receptors In Cisplatin-induced Per...mentioning
confidence: 99%
“…In addition to genetic approaches, pharmacological tools suggest the involvement of TRPA1 and TRPV1 in cisplatin-induced pain behaviours. For example, the pharmacological inhibition of the TRPA1 channel (using the A967079 antagonist) reduced the mechanical and cold allodynia induced by cisplatin in mice, while a TRPA1 agonist (allyl isothiocyanate) at a subnociceptive dose enhanced these behaviours [55]. Furthermore, cisplatin-induced mechanical hypersensitivity was inhibited by silencing TRPA1 and TRPV1 through the intraplantar administration of a membrane-impermeable lidocaine analogue (QX-314) together with TRPV1 agonist (capsaicin) or with TRPA1 agonist, allyl isothiocyanate (AITC) [81].…”
Section: Role Of Ion Channels In Cisplatin-induced Peripheral Neuropathymentioning
confidence: 99%